2018
DOI: 10.1089/jwh.2016.6316
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Cardiovascular Health in Women over the Past Decade: Guideline Recommendations for Practice

Abstract: Cardiovascular disease (CVD) remains the number one cause of death in women. It is estimated that 44 million women in the United States are either living with or at risk for heart disease. This article highlights the recent significant progress made in improving care, clinical decision-making, and policy implications for women with CVD. We provide our perspective supported by evidence-based advances in cardiovascular research and clinical care guidelines in seven areas: (1) primary CVD prevention and community… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 114 publications
(137 reference statements)
1
10
0
Order By: Relevance
“…A further possible limitation could be that our sample included only Andalusian women who had dropped out from CR. Despite that, reasons reported by women are similar of those that have appeared in the literature, allowing to presume similar results in other countries [ 6 ]. The study did not include immigrant women, limiting the ability to comment on reasons for dropout for these participants.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…A further possible limitation could be that our sample included only Andalusian women who had dropped out from CR. Despite that, reasons reported by women are similar of those that have appeared in the literature, allowing to presume similar results in other countries [ 6 ]. The study did not include immigrant women, limiting the ability to comment on reasons for dropout for these participants.…”
Section: Discussionsupporting
confidence: 76%
“…Cardiac rehabilitation (CR) programs are multifaceted interventions designed to optimize clinical outcomes in cardiac patients, focused on exercise, medication management, nutritional counseling, risk factor management, and psychosocial counseling [ 4 ]. CR is considered a Class IA recommendation in clinical practice guidelines for women [ 5 , 6 ]. Empirical evidence has shown that it is effective in reducing morbidity and mortality, improving quality of life in patients with CVD [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…5 The recent guidelines highlighted the consideration of womenspecific risk factors in the history, including gestational diabetes and hypertension, preeclampsia, eclampsia, autoimmune disorders, obstructive sleep apnea, and radiationinduced myocardial injury. 6 The 2016 European Society of Cardiology guidelines for prevention recommend starting systematic CV risk assessment in women from the age of 50 years or after menopause even in case of no known CV risk factor. Women are generally considered at a lower CV risk than men, with a gap of the estimated risk to be approximately 10 years (e.g., the risk of a 60-year-old woman is similar to that of a 50-year-old man).…”
Section: Gender Specificities In Cardiovascular Epidemiologymentioning
confidence: 99%
“…Overall, several health care interventions specifically adapted to women have already proved to be successful. 6…”
Section: Gender Specificities In Cardiovascular Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation